2017
DOI: 10.1177/0267659117723699
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of skin perfusion in venous leg ulcer after exercise

Abstract: Perfusion measurements showed significant changes after three months of regular exercise. We conclude that exercise has a significant effect on tissue perfusion parameters in venous leg ulcer and this effect may play a role in understanding the pathophysiology of VLU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…Eight hundred fifty-three titles were obtained from searches (Figure 1). Five studies met the inclusion criteria, and 1 study was potentially relevant but did not publish healing outcomes . We contacted the corresponding author who confirmed healing outcomes had been collected, and provided us with a prepublication copy of a second article.…”
Section: Resultsmentioning
confidence: 99%
“…Eight hundred fifty-three titles were obtained from searches (Figure 1). Five studies met the inclusion criteria, and 1 study was potentially relevant but did not publish healing outcomes . We contacted the corresponding author who confirmed healing outcomes had been collected, and provided us with a prepublication copy of a second article.…”
Section: Resultsmentioning
confidence: 99%
“…Las intervenciones tuvieron una duración entre siete días a tres meses. Hubo diversidad en el número de sesiones y la forma de entregarlas y ejecutarlas, desde tres sesiones por Skype de 10-15 minutos, con visitas previas en el hogar de 90 minutos (36) (42)(43)(44)(45)47). Y los lugares de entrega fueron clínicas de atención ambulatoria (22,32,(37)(38)(39)(44)(45)(46)(47), hogares de los pacientes y centros deportivos universitarios (41).…”
Section: Componentes Modo Proveedor Y Lugar De Entregaunclassified
“…El hecho de que las intervenciones de ejercicio (20,(35)(36)(37)(38)(39)(40)(41)(42)(43) hayan sido las más frecuentes en la literatura podría explicarse por la evidencia existente sobre la fisiopatología de las UV, aunque no es exacta, se cree que la falla de la bomba muscular de la pantorrilla, que resulta en una elevación sostenida de la presión venosa ambulatoria contribuye a su formación, en comparación con sujetos sanos, los pacientes con IVC tienen una fracción de eyección reducida y un índice de llenado venoso aumentado, lo que indica un deterioro en la capacidad de eyección de la bomba muscular de la pantorrilla así como poca competencia venosa (55)(56). De manera que, los programas de ejercicio que consisten en estiramiento y fortalecimiento de los músculos de las extremidades inferiores junto con ejercicios aeróbicos como caminar, contribuyen a mejorar el retorno venoso, aumentan la movilidad de la articulación del tobillo con el consiguiente fortalecimiento de los músculos de la pantorrilla y la actividad hemodinámica de esta bomba muscular (57)(58)(59).…”
Section: De Franciscis (45) Et Al Italia 2013unclassified
“…They have shown that a 12‐week supervised exercise program improved measures of cutaneous microvascular reactivity in people being treated with compression therapy for venous ulceration. Mutlak and co‐workers (2018) have shown that VLU healing as the size of the ulcer was seen to have decreased significantly in the patients who had performed regular exercise 37 . It appears that the combination of progressive resistance exercises and aerobic activity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The exercise was shown to have a significant effect on VLU healing, particularly when combined with compression therapy. 27 , 37 Patients receiving both compression therapy and progressive tailored exercise training have a higher quality of life. 38 Tew and co‐workers (2018) described that cutaneous microvascular reactivity may facilitate the healing of VLU.…”
Section: Introductionmentioning
confidence: 99%